2020
DOI: 10.2147/nss.s267996
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Sleep Quality and Physical Activity in Saudi Arabian University Students</p>

Abstract: Background: Many studies have documented a strong association between poor sleep quality and physical inactivity. This study evaluates the association between poor sleep quality and physical inactivity among Jazan University students in Saudi Arabia. Methods: An observational cross-sectional study was conducted among undergraduate students at Jazan University. Cluster random sampling was used to select 440 students. The Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire (IPAQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 49 publications
3
38
4
1
Order By: Relevance
“…According to the data, the Faculty of Sports Science and Recreation have good sleep quality probably because of they are still doing virtual exercise activity to fulfil their syllabus requirement which leads to having a good rest. This finding was supported by Mahfouz et al, (2020) which stated that students from universities who frequently exercised showed greater quality of sleep than those who exercised less. Moreover, research done by Badicu (2018) stated that physical exercise, if performed on a daily basis is helpful for the body and may improve the quality of sleep.…”
Section: Discussionmentioning
confidence: 72%
“…According to the data, the Faculty of Sports Science and Recreation have good sleep quality probably because of they are still doing virtual exercise activity to fulfil their syllabus requirement which leads to having a good rest. This finding was supported by Mahfouz et al, (2020) which stated that students from universities who frequently exercised showed greater quality of sleep than those who exercised less. Moreover, research done by Badicu (2018) stated that physical exercise, if performed on a daily basis is helpful for the body and may improve the quality of sleep.…”
Section: Discussionmentioning
confidence: 72%
“…The current study has been carried out to assess the sleep quality among nurses in the National Guard Health Affairs in Al-Medina city, Saudi Arabia, during 2020 (the 1 st year of COVID-19 pandemic) and set recommendations to reduce the burden of the problem among the nurses. Malik et al, 2018 [20], and many other researchers in Saudi Arabia used and assessed the construct validity of the PSQI index among different health-care workers in Jeddah, Riyadh, and Jazan and showed satisfactory results and similar findings as other developed countries who validate the PSQI index in many clinical and subclinical settings [21], [22].…”
Section: Discussionmentioning
confidence: 89%
“…The results are in accordance with those of previous studies. 14,[22][23][24] Studies have shown that physical activity influences sleep through complex interactions involving physiological and psychological pathways. 25 Physical activity benefits sleep regulation by increasing slow-wave sleep in children 26 and promotes sleep quality by improving mental well-being.…”
Section: Discussionmentioning
confidence: 99%